Tip of the iceberg immunohistochemical markers reveal malignant transformation underneath a vocal polyp surface = Vrh ledene sante : maligna transformacija ispod površine glasnica otkrivena imunohistokemijskim markerima - Braut, Tamara; Krstulja, Mira; Marijić, Blažen; Maržić, Diana; Kujundžić, Milodar; Zamolo, Gordana; Vučinić, Damir; Oštarijaš, Eduard (2021)
Novel molecular techniques including markers of laryngeal carcinogenesis could improve the difficult diagnosis of a wide array of laryngeal polypoid changes. The case reported herein shows that not every clinically diagnosed vocal fold polyp is a benign lesion as mostly considered in the literature. Further assessment including carcinogenesis markers detected a nest of micro-invasive squamous cell carcinoma. Therefore, we recommend biopsy backed up with immunohistochemical analysis whenever there is a suspicious polypoid formation in order to exclude or confirm a malignant transformation because of the possibility of multi-focal growth in the active laryngeal epithelium.
Nove molekularne tehnike, uključujući markere laringealne karcinogeneze, mogu pridonijeti diferencijalnoj dijagnozi širokog spektra polipoidnih promjena grkljana. Prikazujemo slučaj koji ukazuje na to da nije svaka klinički dijagnosticirana polipoidna lezija glasnica benigna kao što se obično navodi u literaturi jer smo daljnjom imunohistokemijskom obradom otkrili žarište mikroinvazivnog planocelularnog karcinoma. Stoga kod svake polipoidne tvorbe grkljana preporučujemo biopsiju popraćenu imunohistokemijskom analizom markera kako bi se potvrdila ili isključila maligna transformacija zbog poznate sklonosti multifokalnom rastu u aktivnom epitelu grkljana.
Bibliografija: 38 jed.
Abstract ; Sažetak.
Keywords: Epitelna atipija -- Imunohistokemija -- Molekularni markeri -- Planocelularni karcinom -- Polipi -- Grkljan